Smart Traffic Management at Intersections - Gezim Hoxha; Piotr Gorzelanczyk; RameLikaj; Shaban Thaqi; Flori Cikaqi (Journal of Sustainable Construction Materials and Technologies)
Effective traffic control methods, whether at intersections or other nodes within the road network, play a critical role in ensuring traffic quality and safety. An inappropriate choice of traffic control techniques or poorly optimized light signal programming at intersections often leads to unsatisfactory service levels. This study specifically addresses the issues related to intersections controlled by traffic lights. It aims to identify the key factors influencing the regulation and programming of traffic lights, with a focus on using different microcontrollers, particularly the Raspberry Pi. The primary objective of this research is to develop a methodology and an adapted programming approach to the Raspberry Pi microcontroller to improve traffic performance at intersections and provide sustainable mobility. To achieve this goal, a prototype of a traffic light-controlled intersection was constructed and managed by a Raspberry Pi Model microcontroller. The prototype integrates sensors to collect real-time traffic data, enabling adaptive and efficient signal control. This prototype is now part of the Laboratory of Traffic and Transport at the University of Prishtina. It is used as a model for responsible institutions for motorized traffic management in urban areas. Our findings support scalable deployment in developing countries with minimal infrastructure. Comparative results and reproducible Python code enhance reliability and transparency. The study further includes a comparative analysis of results, presented through diagrams, to evaluate the system’s efficiency.